Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1017/s0043174500074713
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Antidotes on Forage Grass Seedling Response to Metolachlor and Butylate

Abstract: Field studies were conducted for 3 yr near Mead, NE, to evaluate the effectiveness of seed safeners CGA-92194 [N-(1,3-dioxalon-2-yl-methoxy)iminobenzeneacetonitrile], NA (1,8-naphthalic anhydride), and R-29148 (2,2-dimethyl-5-methyldichloroacetyloxazolidine) to reduce herbicide injury to big bluestem (Andropogon gerardiiVitman), indiangrass[Sorghastrum nutans(L.) Nash], intermediate wheatgrass[Agropyron intermedium(Host.) Beauv.], sideoats grama[Bouteloua curtipendula(Michx.) Torr.], and switchgrass (Panicum v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
(24 reference statements)
0
9
0
1
Order By: Relevance
“…Fluxofenin is an oxime ether derivative primarily used to protect grasses from chloroacetanilide herbicides like metolachlor (2,3,13). Griffin et al (12) reported that switchgrass seedlings were safened against metolachlor with 1,8-napthalic anhydride (NA); however, NA is no longer commercially available. There is relatively little research evaluating seed safeners for improved forage establishment (20).…”
Section: Safenersmentioning
confidence: 99%
“…Fluxofenin is an oxime ether derivative primarily used to protect grasses from chloroacetanilide herbicides like metolachlor (2,3,13). Griffin et al (12) reported that switchgrass seedlings were safened against metolachlor with 1,8-napthalic anhydride (NA); however, NA is no longer commercially available. There is relatively little research evaluating seed safeners for improved forage establishment (20).…”
Section: Safenersmentioning
confidence: 99%
“…Seed safeners were proven effective in inducing herbicide selectivity in forages (Griffin et al, 1988). Naphthalic anhydride (NA) (naphthalene-1,8-dicarboxylic anhydride) protected perennial ryegrass (Lolium perenne L.) from alachlor [2-chloro-N-(2,6-diethylphenyl)-N-(methoxymethyl) acetamide] yet failed to protect orchardgrass (Dactylis glomerata L.) from EPTC (S-ethyl dipropyl carbamothioate) or butam [2,2-dimethyl-N-(1-methylethyl)-N-(phenylmethyl)propanamide].…”
Section: Seed Safening From Herbicidal Injury In Switchgrass Establismentioning
confidence: 99%
“…Sand bluestem (Andropogon hallii Hack.) Griffin et al (1988) demonstrated that switchgrass treated with NA and planted to metolachlor-treated fields produced solid stands (55% coverage of planted area) and could prove beneficial when atrazine-tolerant weeds were present in the seeding area. Nash] was protected from EPTC by the proprietary safener CGA-43089 (Abu-Qare and Duncan, 2002).…”
Section: Seed Safening From Herbicidal Injury In Switchgrass Establismentioning
confidence: 99%
See 2 more Smart Citations